1988
DOI: 10.1128/aac.32.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral activated charcoal on tobramycin clearance

Abstract: To evaluate the effect of activated charcoal on aminoglycoside pharmacokinetics, six healthy volunteers received tobramycin intravenously with and without multiple oral doses of activated charcoal. Activated charcoal did not have a statistically significant effect on any pharmacokinetic parameter. We conclude that activated charcoal does not enhance tobramycin clearance in subjects with normal renal function when concentrations in serum are within the therapeutic range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
(19 reference statements)
0
5
1
Order By: Relevance
“…A modest but significant decrease (about 15%) was also noted in the half-life of elimination. These findings are in contrast with the results of tobramycin reported on human subjects (Davis et al 1988).…”
Section: Eflect Of Activated Charcoal In Rf Rabbitscontrasting
confidence: 99%
See 1 more Smart Citation
“…A modest but significant decrease (about 15%) was also noted in the half-life of elimination. These findings are in contrast with the results of tobramycin reported on human subjects (Davis et al 1988).…”
Section: Eflect Of Activated Charcoal In Rf Rabbitscontrasting
confidence: 99%
“…Although in one study it has been observed that charcoal was not effective in enhancing the clearance of a therapeutic dose of the aminoglycoside, tobramycin, in normal individuals (Davis et al 1988), these results cannot be extrapolated to subjects with renal failure (RF) or toxic concentrations of aminoglycosides. A significant effect for charcoal in enhancing digoxin elimination has been demonstrated in Patients with RF, but a relatively small effect was seen in normal subjects (Park et al 1985).…”
mentioning
confidence: 99%
“…Enterally administered compounds are effectively bound due to its large surface and high adsorption capacity thereby preventing systemic uptake from the gastrointestinal tract. A number of pharmacokinetic studies in healthy subjects have been conducted to evaluate the efficacy of antidotes in the management of drug overdose [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…• Multiple-dose activated charcoal therapy did not increase the elimination of astemizole, 31 chlorpropamide, 32 sodium valproate, 33 tobramycin 34,35 and vancomycin. 36 • The elimination half-life of amitriptyline, 37 but not of doxepin 38 or imipramine, 39 was also reduced by multiple-dose activated charcoal in volunteer studies.…”
Section: Volunteer Studiesmentioning
confidence: 97%
“…Davis et al 34 administered tobramycin 2.5 mg/kg intravenously over 30 minutes to 6 volunteers. Davis et al 34 administered tobramycin 2.5 mg/kg intravenously over 30 minutes to 6 volunteers.…”
Section: Reprintsmentioning
confidence: 99%